Leakage Current in P N Junction Diode by Influent from SRFE Process - Narong Sangwaranatee; Itsara Srithanachai; Surasuk Niemcharoen (My University, 2020)
This paper present the effect from soft radiation flash exposure (SRFE) on electrical properties of semiconductor device. SRFE process take only few second on semiconductor device but it quite impact to device performance. The part we will study impact from SRFE such as surface and bulk. COMSOL is tool for help to understand more detail in term of surface recombination, temperature and bulk effect. Surface of device get impact from radiation and temperature generate from radiation. Also, silicon bulk get damage from radiation due to has high penetrate. From electrical results show that leakage current of device has reduce after SRFE process, mean radiation can help to improve or recover damage from fabrication process.
Keywords: Leakage (economics); PIN diode; Integrated Circuits and Semiconductor Failure Analysis